Answer:
x=3
Step-by-step explanation:
Given,
1 = 1/(x-2)
Multiply both sides by (x-2),
1*(x-2) = 1/(x-2) * (x-2)
x-2 = 1
Adding 2 on both sides,
x-2+2 = 1+2
x = 3
Answer:
a.
Step-by-step explanation:
because > means at most < means at least
Answer:
x = 18 ; y = 10 ; z = 102°
Step-by-step explanation:
The triangle in the pic is an isosceles triangle.
As it is an isosceles triangle , it's two sides will be equal .
![= > 3x - 42 = 12](https://tex.z-dn.net/?f=%20%3D%20%20%3E%203x%20-%2042%20%3D%2012)
![= > 3x = 42 + 12 = 54](https://tex.z-dn.net/?f=%20%3D%20%20%3E%203x%20%3D%2042%20%2B%2012%20%3D%2054)
![= > x = \frac{54}{3} = 18](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20x%20%3D%20%5Cfrac%7B54%7D%7B3%7D%20%20%3D%2018)
Also, both the base angles will be equal.
![4y - 1 = 39](https://tex.z-dn.net/?f=4y%20-%201%20%3D%2039)
![= > 4y = 39 + 1 = 40](https://tex.z-dn.net/?f=%20%3D%20%20%3E%204y%20%3D%2039%20%2B%201%20%3D%2040)
![= > y = \frac{40}{4} = 10](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20y%20%3D%20%20%5Cfrac%7B40%7D%7B4%7D%20%20%3D%2010)
According to angle sum property of a triangle , sum of measure of all the angles of a triangle is equal to 180°. So,
![z + 39 + 39 = 180](https://tex.z-dn.net/?f=z%20%2B%2039%20%2B%2039%20%3D%20180)
![= > z + 78 = 180](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20z%20%2B%2078%20%3D%20180)
![= > z = 180 - 78 = 102](https://tex.z-dn.net/?f=%20%20%3D%20%20%3E%20z%20%3D%20180%20-%2078%20%3D%20102)
Answer:
It is a
Step-by-step explanation:
No; we have
. Substituting these into the DE gives
![3x^5=x^5+x^3](https://tex.z-dn.net/?f=3x%5E5%3Dx%5E5%2Bx%5E3)
which reduces to
, true only for
.